Accurate residual stress measurement as a function of depth in environmental barrier coatings via a combination of X-ray diffraction and Raman spectroscopy. Issue 8 (1st June 2020) - Ye, Cheng; Jiang, Peng
Abstract: This study examined the properties of the latest generation of rare earth silicate environmental barrier coating system (EBCs). By combining X-ray diffraction and Raman spectroscopy, a novel and efficient method was developed to measure residual stress in EBCs produced by slurry coating. A 633-nm-wavelength laser beam from the confocal microlaser of a Raman spectrometer was focused on the cross-section of samples, and the spectra were recorded. We performed non-linear multi-peak spectrum fitting with the Lorenz function to obtain the peak shift of the EBC top coat at 5 μm intervals as a function of depth. We then obtained the stress distribution along the depth by calibrating the stress value on the surface via X-ray diffraction. The residual stress in the coating which endured high temperature, water, and oxygen corrosion without serious damage, was non-uniform and compressive. The stress at the bottom of the coating was approximately −275 MPa, decreasing towards the surface. A sudden shift in stress value was observed in the distribution of the residual stress, which was attributed to residual stress relaxation caused by microscopic pores contained within the coating.